Analisis Kemampuan Siswa SDN Banjardowo 1 Jombang dalam Memecahkan Masalah Pecahan - Putri, Himawati Parera; Maf'ulah, Syarifatul; Hartiningrum, Esty Saraswati Nur (Universitas Muhammadiyah Gresik, 2023)
The aim of this research is to describe the fraction problem solving abilities of students with high mathematical abilities at SDN Banjardowo 1 Jombang. This research is a qualitative research. The subjects of this research were class V students at SDN Banjardowo Jombang with one subject with high mathematical abilities. Data collection methods are tests and interviews. The research instruments are the researcher himself as the main instrument and test instruments and interviews as supporting instruments. Checking the validity of the data uses time triangulation. The results of this research are that students at SDN Banjardowo 1 Jombang solve fraction problems according to Polya's steps, namely restating the problem in language they understand while looking at the problem, can state what is known about the problem, can state what is asked about the problem, explain the solution strategy problems that he has written down, can write down the stages of problem solving strategies, re-examine the stages of problem solving, re-examine the results of problem solving, and can draw conclusions from the results of problem solving.